A threefold difference in plant growth response to nitrogen addition between the laboratory and field experiments. Issue 1 (22nd January 2019) - Xu, Xiaoni; Yan, Liming; Xia, Jianyang
Abstract: Quantifying the magnitude of plant response to nitrogen (N) addition is critical in improving our understanding of vegetation productivity in terrestrial ecosystems. Numerous studies under both the laboratory (hereafter lab) and field conditions have shown significant increases in plant growth by N addition. However, differences exist when we integrate or compare the results between N‐addition experiments under the lab and field conditions. Here, we performed a meta‐analysis on observations from 139 field and 127 lab experiments to identify their differences and similarities in the N response of plant growth. Overall, there was a threefold difference in the N effect on plant biomass between the lab (+63.1%) and field (+22.2%) experiments. The magnitude of the lab–field difference varied among plant categories and plant tissues. For example, the larger N effect in the lab than field conditions was about twofold for the herbaceous plant but fourfold for the woody species. Furthermore, the N‐induced increase in biomass was allocated more to above‐ground parts in the field but equally to above‐ and below‐ground parts under the lab conditions. We further showed that these differences were jointly attributed to the differential abiotic (i.e., environmental condition and N application methods) and biotic (i.e., interspecific interaction, age, and functional types) factors under these two experimental conditions. These findings highlight more attention should be paid when the results from the lab experiments are translated to understand the N response of the natural plants.